A community‐of‐care: the integration of a palliative approach within residential aged care facilities in Australia. (6th November 2013) - McVey, Peta; McKenzie, Heather; White, Kate
Abstract In developed countries, residential aged care facilities (RACFs) are increasingly becoming the place of care and site of death for older people with complex chronic illnesses. Consequently, it is becoming ever more relevant for these facilities to provide appropriate complex, as well as end‐of‐life care for this growing group of people. Evidence‐based guidelines for providing a 'palliative approach' were developed and introduced in Australia in 2004, with the emphasis on improving symptom control earlier in the disease trajectory. The aim of the study reported here was to explore the extent to which a palliative approach was being used in the organisation and provision of care for older people with complex needs living in mixed‐level (a combination of low‐ and high‐level care) RACFs. This paper primarily reports on the qualitative findings. Two residential aged care organisations, one in rural New South Wales and the other in Sydney, Australia, participated. Data were collected over a 9‐month period from May until December 2008. Residents, family members and aged care staff were interviewed. Thematic analysis of participant interviews shows that while the various elements of a palliative approach are incorporated into the care of high‐level care residents, the discourse itself is not used. In this paper, we argue for a new conceptualisation of care for people in mixed‐level care facilities: a community‐of‐care, in which a palliative approach is one of several components of the care provided. The findings illuminate aged care staff experiences of providing care to high‐level care residents. They also provide valuable insights into high‐level care residents' perceptions of their health, care provided and the way in which they foresee their care being provided in future. These findings will be important for informing clinical practice, research and policy in these settings.